Strategy of Al Ihsan Islamic Boarding School in Religious Development of the Community in Bontomanai Village, Bontomarannu District, Gowa Regency - Erwin, Erwin; Mahmuddin, Mahmuddin; Nasriah, Sitti (Jurnal Mercusuar, 2021)
The main problem in this research is "How is the strategy of Pondok Pesantren Al Ihsan in fostering religious communities in Bontomanai Village, Bontomarannu Sub-district, Gowa Regency?" and the sub-problems or research questions are: 1) "What is the strategy of Pondok Pesantren Al Ihsan in fostering religious communities in Bontomanai Village, Bontomarannu Sub-district, Gowa Regency?" and 2) "What are the forms of religious fostering carried out by Pondok Pesantren Al Ihsan in Bontomanai Village, Bontomarannu Sub-district, Gowa Regency?". The results of this study show that the strategy of Pondok Pesantren Al Ihsan in fostering religious communities is by conducting religious activities such as routine studies, tabligh akbar, daurah kitab, and organizing i'tikaf during the month of Ramadan. The forms of religious fostering carried out by Pondok Pesantren Al Ihsan are fostering in matters of aqidah, tauhid, sharia, and akhlak.